Performance and technology : practices of virtual embodiment and interactivity - Skoog, Douglas A.; Machon, Josephine (Palgrave Macmillan, 2006)
This exciting and timely collection of writings from international contributors who specialize in a diverse range of digital art and performance practices, surveys various aspects of performance and technology. The discussions interrogate the interaction between new technologies and performance practice. Furthermore, in an innovative way, they link the sensuous contact that must exist between the physical and virtual, together with the resultant corporeal transformation. Not only do bodies morph and (de)morph but their identities consequently become destabilized. In certain technological practices, physicality is both transcended and ludically inscribed - the play (jouer)being all. Consequently, digital practices potentiate creative and aesthetic possibilities and demand new perceptive strategies that not only affirm sensate presence but also 'deceive'. This ground-breaking volume identifies a new performance practice at the cutting-edge of experimentation and, at the same time, explores the evolution of new art practices. Especially, practices that are pivotal in alternative and also mainstream performance and popular culture. Featuring contributions from both key academics and practitioners, this collection will be essential reading for all those interested in the links between new technologies (including motion tracking, artificial intelligence, biotechnology and animation, amongst others) and performance.